Efektifitas Pendidikan dan Dakwah Wasathiyah Melalui Majelis Taklim di Kota Makassar (Studi Pada BKMT Kecamatan Tallo) - Bambang Sampurno; Ahmad Ahmad; Syamsuddin Belo (Universitas Muslim Indonesia, 2022)
Wasathiyah education and da'wah is actually a legacy of the archipelago's scholars who have been embraced and practiced by Muslims in Indonesia. However, after the information technology revolution, where all religious beliefs could be accessed easily and freely by the public, religious teachings that were initially unknown in Indonesia and developed in other countries began to enter and be taught in Indonesia. Including extreme and radical religious teachings that can guide their adherents to carry out terrorist and dangerous acts. The focus of the problem in this paper is (1) the effectiveness of the implementation of Wasathiyah education and da'wah at BKMT, Tallo District, Makassar City., and (2) Supporting and inhibiting factors for the implementation of Wasathiyah Education and Da'wah through BKMT in Tallo District. This paper mentions the fact that the implementation of wasathiyah education and da'wah through the Taklim Council is considered ineffective in creating a moderate and religious community culture. One of the supporting factors is that the religious culture of the Makassar City community is fundamental in accepting educational materials and preaching wasatiyyah openly. The inhibiting factors are apathy, the busyness of various community activities, and the availability of time from the Da'i/Mubaligh to provide spiritual guidance within the framework of religious moderation.